THU0546 Cross-Sectional Analysis of The Associations between Fibromyalgia and Other Chronic Co Morbidities. (15th July 2016) - Lichtenstein, A.; Tiosano, S.; Comaneshter, D.; Cohen, A.D.; Amital, H.
Abstract : Background: The Fibromyalgia syndrome (FMS) has been linked to chronic organic and psychiatric conditions, however large population studies that systematically investigated this claim are scarce (1). Objectives: To evaluate the association of FMS with other common chronic diseases such as psychiatric, rheumatic, cardiovascular, pulmonary and malignant disorders. Methods: Utilizing the database of "Clalit" health services, the largest health maintenance organization (HMO) in Israel serving roughly 4, 000, 000 members, we carried out a cross-sectional study. Fibromyalgia patients were compared to age- and sex- matched controls regarding the coexistence of other chronic diseases. Chi-square and t-tests were used for univariate analysis and a logistic regression model was used for multivariate analysis. Results: The study included 14, 296 patients with Fibromyalgia and 71, 324 age- and sex- matched controls. The proportion of psychiatric disorders (anxiety, bipolar disease, depression, psychoses.) in patients with FMS was significantly higher compared with their proportion in controls (30.1% vs. 12.2% respectively, p<0.001, OR =3.09, 95% CI: 2.96–3.22). The proportion of rheumatic disorders was also significantly higher in FMS patients compared to controls (10.8% and 3.15% respectively, p<0.001, OR =3.73, 95% CI: 3.49–3.99). A multivariate logistic regression model demonstrated that FMS was significantly associated with psychiatric disorders and rheumatic diseases after controlling for confounders, including age, sex, socioeconomic status (SES) and BMI (psychiatric multivariate OR =3.17, p<0.01 95% CI: 3.13–3.21; rheumatic multivariate OR =3.72, p<0.01 95% CI: 3.65–3.79). In contrast, 1365 (1145 controls, 220 FMS) chronic heart failure patients and 1970 (1668 controls, 302 FMS) chronic renal failure patients were not found to be significantly associated with FMS (CHF: OR =0.96, p<0.566 95% CI: 0.83–1.11; CRF: OR =0.90, p<0.098 95% CI: 0.80–1.02). Conclusions: Patients with the FMS have a greater proportion of psychiatric and rheumatic disorders than matched controls. Consequently, physicians treating patients with chronic illnesses in general and rheumatic or psychiatric conditions in particular, should be aware of this high co morbidity rate. References: D. Buskila and H. Cohen, "Comorbidity of fibromyalgia and psychiatric disorders, " Current Science Inc, vol. 11, no. 5, pp. 333–338, Oct. 2007. Disclosure of Interest: None declared